The Effect of Tube Current Variations on Cranium Radiograph Images Using the MATLAB Program - Nurul Auliyaa Hasbi; Asmiati Amir; Muhammad Yunus; Nurul Jannah Jamal; Nurbeti Salam; Muh. Rusli (Postgraduate, University of Mataram, 2025)
Matrix Laboratory (MATLAB) is a software based on matrices, which is easy to use for solving various mathematical and computing problems. This study aimed to determine how variations in tube current (mA) affect the radiographic image of the cranium using the MATLAB program and to assess the program's quantification of this effect. The sample in this study consisted of 3 volunteers who performed AP projection cranial radiography examinations with varying tube current at Pelamonia TK. II Hospital, Makassar. Each sample had the same treatment in patient preparation, examination position, examination projection, and the same exposure factor value, which differed only in the use of tube current values, ​​where the volunteer 1 with 200 mA, the volunteer 2 with 250 mA and volunteer 3 with 320 mA. Measurement of the quality of the AP projection cranium image with tube current of 200 mA, the percentage was 96.11%. At 250 mA, the percentage was 95.00%; at 320 mA, it dropped to 92.78%. It was determined that the optimal tube current variation was 200 mA with the highest percentage in measuring the image quality (density, contrast, sharpness, and detail) of the AP projection Cranium against variations in tube current is almost perfect.